Sociodemographic characteristics, risk factors and genotype distribution of hepatitis C virus in Bosnia and Herzegovina: Single center experience - Ivana Talić Drlje; Božo Šušak; Siniša Skočibušić; Borka Tutiš; Sanja Jakovac; Jurica Arapović (Clinical Epidemiology and Global Health)
Objectives: Viral hepatitis presents a significant public health challenge due to its slow progression leading to severe liver disease and death. The aim of this research is to identify risk behaviors and groups associated with hepatitis C, with the goal of directing prevention measures, increasing mass testing, and potentially facilitating treatment in Bosnia and Herzegovina. Methods: A case-control study was conducted from 2017 to 2022, involving 69 anti-HCV-positive and 70 control respondents matched for gender and age. After obtaining of informed consent, respondents completed a questionnaire focusing on sociodemographic status and potential risk factors for HCV-infection. Molecular quantification tests were carried out, and genotyping was performed for respondents positive for HCV RNA. Results: In this study, we found statistically significantly that anti-HCV respondents are more frequently male, of younger age, with lower educational levels, unemployed, and often unmarried, predominantly residing in urban areas. Behaviors such as tattooing, piercing, contact with others' blood, drug usage, intimate relationships with hepatitis B or C positive partners and having more than two sexual partners in the last 12 months were statistically significantly more common among anti-HCV-positive individuals compared to the control group. However, binary logistic regression analysis identified drug usage as significant risk factor for HCV-infection. Conclusion: Due to the fact that the numbers of drug users are continuously increasing among people of younger age, it is very important to direct prevention measures towards this population.